ROOTED IN CULTURE, MANIFESTED IN CONTEMPORARY DESIGNS: DEVELOPING BRIDAL ADORNMENTS INSPIRED BY SELECTED ANKOLE MOTIFS - Nkiziibweki, Arinaitwe; Mutungi, Emmanuel (Machakos University, 2018)
Creating body adornments rooted in the individual and specific cultures, and integrating them in contemporary designs that come with global fashion of attires and body adornments which are influenced by the Western designers - is the greatest design challenge of African artists. Whereas the indigenous motifs are embedded with meaning intended for that particular community, are colourful and can be a symbol of identity, Africans are torn between the local (usually considered as for the poor) and the imported- “already made” (usually considered high quality and trendy for the rich) yet, Western visitors who come to Africa look for African items such as beads, baskets, mats, pots and carvings. The study developed bridal adornments inspired by traditional exterior decoration motifs of Banyankole in South Western Uganda. The trajectory of this study was that the Banyankole have kept okuhingira(the giveaway ceremony) as an important function yet, body adornments used during okuhingira, do not clearly depict the Kinyankole culture. The study analyzed five Ankole motifs, developed designs of bridal adornments from two selected motifs which were tested for appropriateness with five brides and one salon. Finally, three sets of bridal adornments were produced and put on market. Key words: contemporary designs, bridal adornments, Ankole
Keywords: Contemporary designs; Bridal adornments,